2011
DOI: 10.5603/arm.27670
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Obstructive Sleep Apnea and Chronic Obstructive Pulmonary Disease

Abstract: Background: Obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) may lead to chronic alveolar hypoventilation. The coexistence of OSA and COPD has been termed the ‘overlap syndrome’. The aim of the study was to determine the relationship between the severity of COPD and the occurrence of chronic alveolar hypoventilation in patients with OSA and to evaluate the impact of chronic alveolar hypoventilation in patients with the overlap syndrome on the severity of breathing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Smokers also seem to present more severe OSAHS, at least in the majority of the studies [5,7,[80][81][82][83][84], compared to non-smokers. Numerous OSA indices were deteriorated in smokers including ODI, mean and minimum SaO2, total sleep time and sleep time ratio with SaO2 below 90%, mean apnoea duration, nocturnal hypoxia index and COHb levels [5,7,[80][81][82][83][84][85][86][87][88][89]. However, the relationship of AHI with smoking is not clear.…”
Section: Smoking and Obstructive Sleep Apnoeamentioning
confidence: 92%
See 3 more Smart Citations
“…Smokers also seem to present more severe OSAHS, at least in the majority of the studies [5,7,[80][81][82][83][84], compared to non-smokers. Numerous OSA indices were deteriorated in smokers including ODI, mean and minimum SaO2, total sleep time and sleep time ratio with SaO2 below 90%, mean apnoea duration, nocturnal hypoxia index and COHb levels [5,7,[80][81][82][83][84][85][86][87][88][89]. However, the relationship of AHI with smoking is not clear.…”
Section: Smoking and Obstructive Sleep Apnoeamentioning
confidence: 92%
“…However, the relationship of AHI with smoking is not clear. Many studies concluded that AHI is deteriorated or affected in a dosedependent manner with smoking, even after adjusting for covariates [5,7,[80][81][82][83][84], while in other studies AHI seems not to be related with smoking [85][86][87][88][89][90][91][92]. As far as Epworth sleepiness scale (ESS), the majority of the studies concluded that it is worse in smokers [80,82,85,87], although there were also a few notable exceptions in this topic [7,91].…”
Section: Smoking and Obstructive Sleep Apnoeamentioning
confidence: 99%
See 2 more Smart Citations